Research and design of the moving system for the cobalt-60 industrial irradiator - Le , Minh Tuan; Tran , Khac An; Cao , Van Chung; Phan , Phuoc Thang (Nuclear Science and Technology, 2016)
On the way of localization of Cobalt-60 industrial irradiators, Research and Development Center for Radiation Technology (VINAGAMMA) has successfully designed and manufactured the first version of Co-60 industrial irradiator, VINAGA1. The second version of Co-60 industrial irradiator has been studied and designed by VINAGAMMA in the frame of the scientific project No. ĐTCB.02/15/TTNCTK. The nucleus of a Co-60 industrial irradiator is a mechanical system inside an irradiation room namely a tote box moving system. This report presents the tote box moving system designed by VINAGAMMA. The tote box moving system contains 52 tote boxes with the dimensions of 50 cm (w) × 70 cm (l) × 150 cm (h) that are moving around the source racks in the manner of 4 passes and 2 levels. The irradiator with this tote box moving system has good specifications: The minimum time of an irradiation cycle is 1h 20 min. and the dose uniformity ratio (DUR) at the product densities of 0.1 g/cm3 and 0.5 g/cm3 is 1.4 and 1.8, respectively. Radiation energy utilization efficiency at the product densities of 0.1 g/cm3 and 0.5 g/cm3 is 19.7% and 48.8%, respectively. These specifications meet the requirements for a multi-purpose Co-60 industrial irradiator and the present irradiation requirements in Vietnam.